A Study of Senake Bandaranayake Classification Scheme for the Archaeology and Related Disciplines - Rathnabahu, R.M.N. (Department of Library and Information Science, Faculty of Social Sciences, University of Kelaniya, Sri Lanka, 2016)
There are two types of classifications, one is the general classification scheme which covers all subjects while the special classification scheme which covers a subject or single subject bundle. Above general classification schemes apply in general libraries like university, public, national and so on where as special libraries tend to use special classification schemes. Single subject based or special libraries are facing many problems when using general schemes. However due to several reasons, special libraries have to use general classification schemes. Therefore, the principal purpose of this paper is to study a special collection namely, SenakeBandaranayake Classification scheme (SBC) introduced to the Library of the Postgraduate Institute of Archaeology (PGIAR), Sri Lanka. The SBC is simple, usable and special library classification system. Neither the Dewey Decimal Classification (DDC) nor the Universal Decimal Classification (UDC) are suitable for classifying an archaeological collection. Therefore, late Prof SenekeBandaranayake developed this system in classifying the archaeology and its related subject materials.Later this PGIAR Classification System was named as a SenakeBandaranayake Classification by the Senior Assistant Librarian of the Postgraduate Institute of Archaeology (PGIAR) in year 2010 in honor of his devotional dedication to the development of this system. Forth version of SBC system is currently using at present and it was edited on 30th December 1995. The SBC organizes library materials by three main classes namely, General Subjects (A), Archeology (B) and Region or country specific material (C). The notations in section A and section B are purely non numerical. Letters of the English language are used as symbols. The two major sections namely, A and B are subdivided into board subject areas by addition of a second letter to the notation. Further subdivisions have indicated by the third letter notation. Decimal uses for creating further divisions. Following example will described the situation; B- Archaeology, BC-Techniques, BCB.Ex-Excavations. Third category section C, are assigned a numerical notation of four digits. Further specification is achieved by division of the whole number in a hierarchical pattern i.e 3608 Sri Lanka. These area numbers are combined the classification numbers of either section A and B as appropriate i.e “Sri Lankan Philosophy” is classified as 3608 AC. Rules and regulations and guidelines for classification are incorporated in main volume to make numbers. Further, Index to SBC also available. SBC is able to accommodate new subjects. No tables are indicated.This is overall classification system and not for all divisions and subdivisions have been finalized. These will be developed as the collection grows. Currently The Libraries of PGIAR, the Central Cultural Fund and Department of Archaeology are using this system.
Keywords: Classification; Library classification; Special classification; SenekeBandaranayake Classification; Archaeology; Bibliographic control; Knowledge organization